KEWENANGAN BERBAGAI INSTANSI DI PELABUHAN TANJUNG EMAS, SEMARANG JAWA TENGAH - Harun Al Martohandoyo; Budhi Hascaryo Iskandar; John Haluan; M. Fedi A. Sondita; Hasjim Djalal (Buletin PSP, 2007)
Tanjung Emas Port of Semarang Central Java is one of international ports in Indonesia. Some state-institutions play role as hold of authority in this port. This paper describes about the authorities of the institutions in the port. Based on the descriptive analysis, it is showed some overlapping in authorities among the institution in the port. This fact arises some unclear condition among stake holders, especially enterpreuner who run the buiseness engaged with the port